Going Up: Real Estate Is on the Rise Again in Japan - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2006)
Nothing symbolizes Japan's bubble economy, or its subsequent long slump, more than real estate. Now, after dropping by as much as 70%, real estate prices are ticking up, signaling a renewed Japanese economy. A major restructuring of the nation's financial system, along with an injection of foreign capital and the introduction of publicly traded real estate investment trusts, are driving the real estate revival, according to Wharton faculty and real estate analysts working in Tokyo.